A study on the doctors’ medical practices on YouTube and its impact on the nature of the work - A perspective from Bangladesh - Rahman, Maruf; Rashid, Mohammed; Rahman, Mohammad Kasifur (Technium Social Sciences Journal, 2025)
This paper discusses the journey of a South Asian country, Bangladesh, towards a digital nation, along with its focus on the digital health sector. Due to inadequate ICT infrastructure, people seek and share health-related information on search engines and social media, such as Google and Facebook and watch health issues related YouTube Videos. This paper argues that while the advancement of digital media technology opens the opportunity for digital labor by enabling doctors to work in the digital space and allows them an extra earning facility, it exploits the free labor of the viewers who participate in digital media platforms. To examine how the digital media platform exploits free labor in digital space, this study analyzes one doctor’s (Dr Jahangir Kabir) YouTube channel and explores the digital behavior of the people through a close reading of digital activities such as watching videos, liking content, commenting, and subscribing to the channel. After analyzing the digital activities of content creators and viewers on YouTube, this paper unpacks how YouTube is biased in monetizing certain activities based on their eligibility requirements for monetization, for example, having at least one thousand subscribers and four thousand watch hours in the past twelve months but it has no policy who watches those contents and subscribe the channels. To understand the biased and exploiting free labor notion of YouTube, this study explores the scholarships and literature on the intersection of social media studies, digital labor studies, and digital health.